Specific Symptoms of Thyrotoxicosis in Japanese Patients: A Reevaluation of Classical Symptoms in Modern Thyroid Function Tests. (27th September 2016) - Tagami, Tetsuya; Tsuiki, Mika; Nakao, Kanako; Nakatani, Rieko; Kakita, Maiko; Ueda, Yohei; Matsuo, Naomi; Usui, Takeshi; Naruse, Mitsuhide; Shimatsu, Akira
Abstract : Background: Medical interview of patients can yield clues for the detection of thyroid dysfunction. However, symptoms of thyrotoxicosis as described in textbooks are based on Western populations. Aim: To elucidate specific symptoms of thyrotoxicosis in Japanese patients. Methods: For one year, consecutive patients who visited us for their first medical examination were asked to complete an original questionnaire about their overall complaints. Results: Excluding patients who were already being treated for thyroid dysfunction, 267 subjects were analyzed: 67 overt hyperthyroid patients (T), 11 with subclinical hyperthyroidism (ST), 30 hypothyroid patients (H), 25 with subclinical hypothyroidism (SH), and 134 euthyroid subjects (E). Seven symptoms were cited by more than 70% of the patients in T and four were cited by more than 70% of subjects in ST. However, more than half of the subjects in E cited 'heat intolerance' and 'easy fatigability', indicating that these are considered as nonspecific and indefinite complaints to detect thyrotoxicosis. The mean severity of 19 symptoms was significantly higher in T than in E, and ROC analysis was moderately accurate at distinguishing T from E in four symptoms of 'palpitation', 'shortness of breath', 'body weight loss', and 'tremor'. Conclusions: Four symptoms — 'palpitation', 'shortness of breath', 'body weight loss', and 'tremor' — are thought be the most useful for efficiently detecting thyrotoxicosis.